Analisis Pengembangan Usaha Home Industry Pengolahan Kopi Tolaki di Desa Tridana Mulya Kecamatan Landono Kabupaten Konawe Selatan - Azzahra, Marwah; Abdi, Abdi; Dirgantoro, Muhammad Arief (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2019)
Kopindo Sukses Bersama's home industry business the processes coffee beans into ground coffee with the Tolaki Coffee product brand, this business has been known at the provincial level of Southeast Sulawesi, it takes A good business strategy to face business competition increasingly complex and competitive. Therefore, the objectives of this study are: (1) To find out the identification of internal factors and external factors of business development, Kopindo Sukses Bersama home industry, (2) To find out the business development strategy of Kopindo Sukses Bersama Home Industry in the Village of Tridana Mulya. The method used in this study is quantitative and qualitative methods.This research was conducted in Tridana Mulya Village, Landono Subdistrict, south Konawe Regency, Techniques for collecting data through observation, interviews, and literature. Data analysis uses the Grand Strategy and SWOT matrix. Research results based on the grand strategy matrix analysis of the internal environment coordinate point 2.102 and the external environment 2.476 means that the business position is in quadrant I. that is the application of aggressive strategies, The strategy that must be implemented is the SO strategy by using all the power to seize and take advantage of the maximum opportunities.